Magnetic and structural properties of CoFeB thin films grown by pulsed laser deposition. (23rd October 2020) - Awana, Geet; Cox, Chris; Venkat, Guru; Morrison, Kelly; Zhou, Zhaoxia; Backes, Dirk
Abstract: The emergence of thin film CoFeB has driven research and industrial applications in the past decades, with the magnetic random access memory (MRAM) the most prominent example. Because of its beneficial properties, it fulfills multiple functionalities as information-storing, spin-filtering, and reference layer in magnetic tunnel junctions. In future, this versatility can be exploited beyond the traditional applications of spintronics by combining with advanced materials, such as oxide-based materials. Pulsed laser deposition (PLD) is their predominant growth-method, and thus the compatibility of CoFeB with this growth technique will be tested here. This encompasses a comprehensive investigation of the structural and magnetic propoperties. In particular, we find a substantial 'dead' magnetic layer and confirm that it is caused by oxidation employing the x-ray magnetic circular dichroism (XMCD) effect. The low damping encountered in vector network analyzer-based ferromagnetic resonance (VNA-FMR) renders them suitable for magnonics applications. These findings demonstrate that CoFeB thin films are compatible with emergent, PLD-grown materials, ensuring their relevance for future applications.